Evaluating The Effectiveness of The Intercultural Communication Needs (ICN) Model on Developing Intercultural Competence Among Iranian EFL University Students - Vahid Ghorbani (Journal of English Language Teaching and Applied Linguistics, 2026)
Background: Intercultural communicative competence (ICC) has become a central objective in English as a Foreign Language (EFL) education due to increasing global interaction. However, EFL instruction in Iran has traditionally prioritized grammatical and lexical accuracy, offering limited opportunities for intercultural development. To address this gap, the Intercultural Communication Needs (ICN) model integrates three core macro-needs, language, emotion, and culture, into instructional practiceAims: This study examined the effectiveness of the ICN model in enhancing ICC among Iranian university EFL learners.Methods: A quasi-experimental pretest–posttest design was employed with 100 undergraduate students divided into experimental and control groups. Over a six-week period, the experimental group received ICN-based instruction, while the control group followed conventional EFL instruction. Data were collected using a researcher-developed 15-item ICC questionnaire measuring linguistic, emotional, and cultural needs. Paired-samples and independent-samples t-tests were conducted, and effect sizes were calculatedResults: The results indicated a significant improvement in the experimental group’s overall ICC, with a large effect size (Cohen’s d = 1.735). Among the ICN components, language showed the greatest gains, followed by emotion and culture. In addition, students reported increased confidence, empathy, and curiosity toward intercultural interactionConclusion: The findings provide empirical support for the ICN model as an effective pedagogical framework for fostering holistic intercultural competence in EFL contexts and highlight the importance of integrating linguistic, emotional, and cultural dimensions in language instruction.